P09 FIGO 2018 stage IB2 (≥2 to <4 cm) cervical cancer treated with neoadjuvant chemotherapy followed by fertility sparing surgery (CoNteSSa)/Neoadjuvant chemotherapy and conservative surgery in cervical cancer to preserve fertility (NeoCon-F). (1st November 2019) - Plante, M; van Trommel, N; Lheureux, S; Oza, A; Wang, L; Sikorska, K; Ferguson, S; Han, K; Amant, F
Abstract : Introduction/Background: There is limited data regarding the optimal management of premenopausal women with cervical lesions measuring ≥2 to<4 cm who desire to preserve fertility. Methodology: Study hypothesis: Neoadjuvant chemotherapy (NACT) will be effective in reducing the size of the tumor and will enable fertility-sparing surgery (FSS) without compromising oncologic outcome. Primary objective : To evaluate the feasibility of preserving fertility. Secondary objectives : To evaluate response rate to NACT, surgical complications and rate of FSS, overall survival up to 3 years for patients who completed NACT and FSS. Trial design: Premenopausal women diagnosed with stage IB2, ≥2 to <4 cm cervical cancer who wish to preserve fertility will receive 3 cycles of platinum/paclitaxel chemotherapy. Patients with complete/partial response (residual lesion <2 cm) will undergo FSS. Patients will be followed for 3 years to monitor outcome. Patients with suboptimal response (residual lesion ≥2 cm) will receive definitive radical hysterectomy and/or chemoradiation. Major eligibility criteria: Patients must have histologically confirmed invasive cervical cancer, ≥2 to <4 cm lesion by clinical evaluation and MRI, negative nodes and premenopausal (≤40 years old). Following 3 cycles of NACT, patients must achieve a complete/partial response. Exclusion criteria include high-risk histology, tumor extension to uterine corpus/isthmus (as per MRI) and suboptimal response/progression following NACT. Results: Primary endpoints: Assess the rate of functional uterus defined as successful FSS and no adjuvant therapy. Exploratory objectives: Evaluate patients reported outcome and quality of life, ovarian function and rate of pregnancy during follow-up period (3 years). Translational research part is included. Conclusion: This is a Phase II, prospective international trial. 90 evaluable patients will be needed to complete the study. A stopping rule will be activated if the recurrence rate at 2 years exceeds 10%. Activation is planned for the summer 2019. Disclosure: Nothing to disclose.